Learning styles and motivations in learning English amongst English as second language foundation students at a public university in Selangor, Malaysia / Leele Susana Jamian, Azean Abu Samah and Norazah Abdul Aziz - Jamian, Leele Susana; Abu Samah, Azean; Abdul Aziz, Norazah (Universiti Teknologi MARA, 2022)
The reformation of education is a dynamic process that requires a constant investigation and research particularly in the 21 st century. In view of performance in the second language (L2), various variables were measured consistently by many scholars globally and among them, are learning styles, self-efficacy, and motivations. However, these variables are normally measured individually in past studies. Also, due to the pandemic of COVID-19 worldwide, the study of motivations amongst ESL learners is paramount in facing the challenges of online learning. Drawing from an in-depth study investigating the relationship of learning styles and self-efficacy toward motivations amongst the ESL Foundation students in public universities in Malaysia, this paper focuses only on measuring the statistical relationship between learning styles and motivations in learning English amongst the ESL foundation students at one of the public universities in Malaysia. A mixed-methods research design was employed in the current study. Guided by four research questions using a descriptive-correlational research design, mainly the study explored the relationship amongst 117 ESL respondents. Reid’s PLSPQ and Gardner and Lambert’s AMTB instruments were used to collect the quantitative data. Findings indicated that most of the students rated themselves as having flexible learning styles and high level of motivations. Also, there was a significant and positive relationships between learning styles and motivations (R=.464) and the simple regression test showed that 21.5% (R 2 =.215) of the variance in Motivations score was predicted from learning styles dimensions. Lastly, qualitative findings tend to corroborate the quantitative findings. Thus, all these findings lead to some various important implications to stakeholders.